Sewage Sludge-Induced Effect on Growth, Enzyme Inhibition, and Genotoxicity can be Ameliorated Using Wheat Straw and Biochar in Pheretima posthuma Earthworms - Khalid, Hira; Kashif Zahoor, Muhammad; Riaz, Danish; Arshad, Madeeha; Yaqoob, Rabia; Ranian, Kanwal (Frontiers in Environmental Science, 2022)
Sewage sludge, being rich in organic matter and nutrients is widely used as fertilizer to increase the fertility of soil. The direct application of sewage sludge without any treatment cause soil contamination as well as significantly affects the earthworm populations. In the present study, effect of sewage sludge amended soil on growth, enzyme activities, and the DNA damage in Pheretima posthuma earthworms were studied under wheat straw and biochar treatment of 30-day laboratory incubation. Wheat straw, biochar, and sewage sludge were applied at 0 (control), 5, 10, and 25% w/w along with combined treatment of sewage sludge with biochar and wheat straw, respectively at 25% each. After the incubation period, percent change in mean weight and length was measured whereas esterases and phosphatases enzyme activities were quantitatively determined. RAPD-PCR and Comet assay were performed to assess the genotoxicity. A significant weight loss was observed (26%) at a 25% rate of sewage sludge and biochar (11%), respectively. Similarly, a maximum length decrease was observed with sewage sludge (2.5%) followed by biochar (0.80%) at a 25% application rate. Mean weight and length both decreased with increasing the rate of sewage sludge and biochar. In addition, there was no change observed in the weight and length of P. posthuma in the treatment consisting of sewage sludge and wheat straw. Moreover, sewage sludge caused inhibition of esterases and phosphatases activities as well as induced DNA damage. The comet parameters showed that wheat straw and biochar ameliorated the toxic effects of sewage sludge. It is, therefore, concluded that sewage sludge has a tangible impact on earthworms which ultimately disrupt ecosystem functions and wheat straw can thus be utilized to reduce the toxicity of sewage sludge in Pheretima posthuma earthworms.